The effect of dopant and optical micro-cavity on the photoluminescence of Mn-doped ZnSe nanobelts - Zhou, Weichang (Springer, 2013)
Pure and Mn-doped ZnSe nanobelts were synthesized by a convenient thermal evaporation method. Scanning electron microscopy, X-ray powder diffraction, energy dispersive X-ray spectroscopy and corresponding element mapping, and transmission electron microscope were used to examine the morphology, phase structure, crystallinity, composition, and growth direction of as-prepared nanobelts. Raman spectra were used to confirm the effective doping of Mn(2+) into ZnSe nanobelts. Micro-photoluminescence (PL) spectra were used to investigate the emission property of as-prepared samples. A dominant trapped-state emission band is observed in single ZnSe(Mn) nanobelt. However, we cannot observe the transition emission of Mn ion in this ZnSe(Mn) nanobelt, which confirm that Mn powder act as poor dopant. There are weak near-bandgap emission and strong (4)T(1) → (6)A(1) transition emission of Mn(2+) in single [Formula: see text] and [Formula: see text] nanobelt. More interesting, the (4)T(1) → (6)A(1) transition emission in [Formula: see text] nanobelt split into multi-bands. PL mapping of individual splitted sub-bands were carried out to explore the origin of multi-bands. These doped nanobelts with novel multi-bands emission can find application in frequency convertor and wavelength-tunable light emission devices.